Madame du Châtelet, leibniziana malgrè Voltaire. - Macarrón Machado, Ángeles (THÉMATA. Revista de Filosofía, 2009)
Gabrielle-Émilie du Châtelet publicó Institutions de Physique en 1740, un manual de física en el que se complementaba el pensamiento newtoniano —la física triunfante en ese momento— con la metafísica de Leibniz-Wolff. La marquesa, que traduciría al francés los Principia de Newton, había incorporado el pensamiento leibniziano a su manera de entender la realidad. Voltaire, su compañero sentimental e intelectual, positivista avant la lettre, nunca pudo aceptar la deriva intelectual de su amiga. Gabrielle-Émilie du Châtelet published Institutions de Physique in 1740, manual of physics which complemented the newtonian theorie —the dominant physics at the time— with the Leibniz-Wolff's metaphysics. The marquise, who was to translate the Principia de Newton, had incorporated leibnizian thought in accordance with her world view. Voltaire, her lover and intellectual partner, positivist avant la lettre, was never able to accept the intellectual course taken by his friend.